The practice of water aerobics with the elderly: Physical and psychological aspects - Martins, Victoria; Lima, Gustavo de Sá Oliveira; Silva, Leonardo Pereira da; Silva, Angélica Gomes da; Bastos, Adriano Domingues; Coêlho, Pedro Gabriel Dias; Noleto, Diandra Carvalho de Sá; Borges, Dângela Bezerra de Sena; Nascimento, Marcos Antonio do; Lourenço, Bruna dos Santos (Seven Editora, 2023)
This Chapter addresses the content on the practice of physical activities by the elderly in the aquatic environment, more specifically water aerobics. It will discuss the importance of water aerobics socially and physiologically for the elderly and its main benefits; from the prevention to the treatment of diseases that are linked to the aging phase. Worldwide, there is a notorious increase in the population aging process, so it is necessary to perpetuate good eating habits and physical activities, so that this phase is not associated with an increase in pathological conditions. Regarding these practices, water aerobics gives back to the elderly autonomy, self-esteem, greater social bond with new friendships during classes; In addition to physiological benefits such as; improvement of muscular endurance, increase of strength, flexibility, improvement of physical skills and capacities, among others. In this Chapter we will also see that water aerobics brings in its practical proposal, the use of music and the diversity of materials, making it even more pleasurable, playful and special for the elderly. With all its differentials and facilities of execution and good adaptation by this public, this activity also helps to return more quality of life to patients in the treatment of diseases such as ankylosing spondylitis and lymphedema. Therefore, it is concluded that the practice of water aerobics is an excellent alternative for health promotion, prevention and treatment of diseases in the elderly. DOI:https://doi.org/10.56238/innovhealthknow-048